Hiv/Aids Treatment And Health-Related Quality Of Life: Patients’ Perspective And Impact Of Adverse Drug Reactions Among Hiv/Aids Patients - Ahmed, Syed Imran (2015)
Advancements in antiretroviral treatment (ART) and shift of HIV as a chronic infection, presents challenges, including adverse drug reactions (ADRs) affecting adherence and retention to care as well as health related quality of life (HRQoL); thus evaluation of ADRs and measures of HRQoL is imperative to maximize the overall treatment outcomes. In addition, greater involvement of the patients in their medical care can benefit treatment outcomes, thus understanding patients’ knowledge and beliefs towards disease, treatment and related issues are essential elements in overall HIV care. The present study was carried out at Hospital Sungai Buloh. Four hundred and forty three Malaysian HIV/AIDS patients, using Antiretroviral Therapy (ART) for at least three months, participated in this study. The data were analyzed using the Statistical Package for Social Sciences (SPSS®) version 18 and STATA IC® version 12. Qualitative methodology was used to explore patients’ perspectives on the disease, treatment and care with the help of a semi structured interview guide. A saturation point was reached after the 13th interview. All interviews were audio-recorded and subjected to a standard content analysis framework.